MENINGKATKAN PEMAHAMAN SISWA MENGENAI MATERI LUAS DAN KELILING LINGKARAN DENGAN PENERAPAN TEORI BELAJAR JEROME BRUNER - Khasanah, Noor; Purwaningrum, Jayanti Putri (Universitas Muhammadiyah Surabaya, 2023)
Until now, the students' comprehension ability in learning mathematics in Indonesia is still low. This can be proven by the observations made by Winda Agustina, and her friends at MTs Al Falah Mahe class VIII, during the learning process of the circle material in the sub-chapter area and circumference of the circle. From these observations, it is known that the cause of the backward understanding of students regarding the Mathematics Learning material in the area and circumference of the circle sub-chapter is that teachers tend to provide direct material / lecture methods, and students are not given the opportunity to find the formula for the concept of area and circumference of the circle by themselves. So as a result, many students have difficulty understanding the material directly and the value of student learning evaluation results is still low / below the KKM (Minimum Completeness Criteria). If the problem is not immediately addressed, it will greatly impact the learning process and student learning outcomes in the classroom which will decline. From this, the writer tries to find a solution to find out how to improve students' understanding of mathematical concepts, especially regarding the broad chapter and the circumference of the circle in applying Bruner's theory.